Liver Transplantation in Rescue Allocation: Comparison of the Donor Risk Index, Balance of Risk Score and Graft Function After Liver Transplantation - Silveira, Fábio; Porto Silveira , Fábio; Silveira, Cassia Regina Sbrissia; Montero, Ana Sofia; Higa, Henrique Cesar; Ruzzon, Arthur; Schulz, Ricardo Teles (Brazilian Journal of Transplantation, 2023)
Background: In the model for end-stage liver disease (MELD) system, the use of livers from rescue allocation (RA), those refused for the first five of the ranking, have conflicting results in the literature. Objective: Analysis of the characteristics of the different simulated patterns of allocation (pattern vs. rescue), using the donor risk index (DRI), the balance of risk score (BAR) and its impact on the graft function. Method: Cohort of 233 liver transplants in adults, performed between 2015 and 2022. Results: General characteristics, age 50.3 ± 11.8 years; 64.81% CHILD C; MELD in allocation 22.4 ± 7.6. Initial graft dysfunction in 12.45% and primary nonfunction (PNF) in 8.15%; with DRI 1.41 ± 0.32. Transplants in RA occurred in 18.03% (n = 42) of cases, in patients with significantly lower MELD (18.4 ± 4.8) and BAR (7.1 ± 3.2) compared to standard allocation (23.2 ± 7.9; 9.2 ± 4.2 respectively). The DRI was significantly higher (p = 0.001) in the RA (1.58 ± 0.37). Age (p = 0.23) and body mass index (p = 0.85) of the donor, cold ischemia time (CIT) (p = 0.10) showed no differences between the groups. RA organs came more often from out-of-state (50% vs. 2.62%) and less harvested by our surgical team (38.1% vs. 79.0%). Early graft dysfunction (EGD) in 16.67% (n = 7); 14.29% (n = 6) of primary nonfunctioning in the RA group, percentage higher than in the standard allocation group with 11.52% (n = 22) and 6.81% (n = 13) respectively; however, there was no difference with statistical significance (p = 0.052). There was no difference in survival (73.81% vs. 72.25%; p = 0.83). Conclusion: A strategy more frequently employed in patients with less severe conditions according to BAR score, liver grafts in a RA rescue allocation system had higher DRI scores and did not provide a difference in short-term survival.